Estudo sobre a formação da solução sólida em filmes finos de zrn+si depositados via magnetron sputtering reativo - Santos, Júlio César Valeriano dos (2023)
ZrN thin films with 1.6% Si addition were deposited via reactive magnetron sputtering and characterized by RBS, SEM-FEG, GAXRD, XPS and high temperature oxidation tests, aiming to investigate how structurally silicon is inserted in ZrN matrix. GAXRD analyses show a reduction in lattice parameter and grain size due to Si incorporation and XPS analyses demonstrate Si is present in nitride form. Such observations suggest the non-formation of substitutional or interstitial solid solution with ZrN, but the presence of Si3N4, even in low Si concentrations.